Study on multi-phase structured icephobic constructions - Wu, Mengjuan (2023)
The accumulation of ice on critical infrastructure, such as aviation, telecommunication, electricity, and transportation systems, can cause severe disruptions to daily life and significant economic losses. While applying icephobic coatings has been proposed as a potential solution, the challenge remains in creating coatings that can effectively withstand adverse environmental conditions, and also demonstrate a long service life and mechanical durability. The motivation of the work is to provide a comprehensive analysis of the fundamental aspects related to icephobicity research, and to explore novel, durable icephobic materials and surfaces, to produce well-rounded research outcomes.